Banten Jejanganan dalam Upacara Tiga Bulanan di Kota Mataram - Sumari, Made (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Banten jejanganan was used in tiga bulanan ceremony by Hindus in Mataram City. It has been a tradition until now, but Hindus do not fully know and understand its form, function, and meaning. This research aimed at obtaining answers to this matter. It used a descriptive qualitative approach. The research was conducted in Mataram City. The data were collected by observation, interview, and study of document. Data were analyzed by using data reduction, classification and data display, conclusion, and verification. The research findings were: 1) the form of Banten jejanganan in tiga bulanan ceremony in Mataram City was a unified form consisting of various elements; the banten arranged by appropriate process, 2) the functions of the banten jejanganan were as a form of offering to Ida Sang Hyang Widhi (God) and His Manifestations as the sang catur sanak; sang catur sanak had functions in protecting, guarding the baby from the womb until the baby gave birth in the world safely and healthily; catur sanak was also as purification for the baby her/himself and also as the purification to baby’s parents. 3) The meaning of banten jejanganan was a symbol of sacred power of the existence of Ida Sang Hyang Widhi as the Almighty, banten jejanganan had meaning as a symbol of thanks to God for His blessings; it also had meaning as symbol of thanks to catur sanak for taking care the baby. The birth of baby cannot be separated from the support of the parents in guarding, caring for, and carrying out this ceremony by upakara yadnya.